Investigations on compensated ferrimagnetism in the Mn2Co0.5V0.5Al Heusler alloy. (March 2020) - Gavrea, R.; Hirian, R.; Isnard, O.; Pop, V.; Benea, D.
Abstract: We present theoretical and experimental investigations on the electronic and magnetic properties of the Mn2+δ Co0.5-δ V0.5 Al (δ = 0 ÷ 0.08) and Mn2+z Co0.5 V0.5-z Al (z = −0.14 ÷ 0.08) Heusler alloys. The electronic band structure calculations by the Korringa-Kohn-Rostoker (KKR) Green's function method show the dependence of the total spin moment on the preferential site occupation for different crystal sites and predict compensated ferrimagnetic behavior for the compounds obtained from Mn2 Co0.5 V0.5 Al by slight variation of composition. Experimental investigations by tuning the Mn content in Mn2 Co0.5 V0.5 Al alloys have been performed in order to achieve the fully compensated ferrimagnetic behavior which is of particular importance for spintronics. The thermo-magnetic measurements show different types of ferrimagnetic behavior with the threshold influenced by Mn content: N-type of ferrimagnetic behavior for Mn2+δ Co0.5-δ V0.5 Al, while for the Mn2+z Co0.5 V0.5-z Al Heusler alloys a combined N/P-type of behavior, depending on z, is observed: N-type for Mn excess/P-type for Mn deficiency. The Curie temperatures of the investigated alloys show high sensitivity on the Mn content. The results of our study may give an insight on the influence of the composition on the magnetic properties of the Mn2 Co0.5 V0.5 Al alloys in order to adjust their properties and make them suitable for spintronic applications. Highlights: Compensated ferrimagnetism in Mn2 Co0.5 V0.5 Al Heusler alloys by tuning composition. N/P type of thermomagnetic behavior in Mn2+z Co0.5 V0.5-z Al. P type of thermomagnetic behavior in Mn2+δ Co1-δ V0.5 Al. The Curie temperatures are highly compositional sensitive. Mn1.96 Co0.5 V0.54 Al alloy close to the fully compensated ferrimagnetic behavior.